New Music Ensemble - Wolter, Mike (My University, 2010)
Over the past two years, Dr. Ethan Wickman and I have collaborated on developing an Eau Claire New Music Ensemble. During the summer of 2009, with help from a grant from ORSP, Dr. Wickman and I were able conduct research within the university as well as investigate similar groups in universities around the country. Our research has yielded a sustainable plan for structuring the ensemble, managing repertoire, and encouraging faculty-student relations.
Color poster with text and images.
Keywords: Eau Claire New Music Ensemble; Music--Wisconsin--Eau Claire; Performance art--Wisconsin--Eau Claire; Musical groups--Wisconsin--Eau Claire; Posters